GE_GERICHTE P/5429/2017 vom 7. Juli 2022 - GE Cour de justice (2022)
ORDONNANCE PÉNALE;OPPOSITION(PROCÉDURE);DÉFAUT(CONTUMACE);EMPÊCHEMENT(EN GÉNÉRAL);EXCUSABILITÉ;PROCÉDURE ORALE;CIRCONSTANCES PERSONNELLES | CPP.66; CPP.343; CPP.356